Lobeline for smoking cessation - Stead, Lindsay F; Hughes, John R (Cochrane database of systematic reviews, 2012)
Lobeline is a partial nicotine agonist, which has been used in a variety of commercially available preparations to help stop smoking. The objective of this review was to assess the effects of lobeline on long term smoking cessation. We searched the Cochrane Tobacco Addiction Group trials register (most recent search December 2011). Randomized trials comparing lobeline to placebo or an alternative therapeutic control, which reported smoking cessation with at least six months follow-up. We extracted data in duplicate on the type of subjects, the dose and form of lobeline, the outcome measures, method of randomisation, and completeness of follow-up. We identified no trials meeting the full inclusion criteria including long term follow-up. One large trial failed to detect any effect on short-term abstinence. There is no evidence available from long term trials that lobeline can aid smoking cessation, and the short-term evidence suggests there is no benefit.